Pelatihan Teknik Menulis Copywriting Melalui di Media Sosial Untuk Meningkatkan Daya Tarik Calon Pelanggan Produk UMKM Di Rt 03 Rw 06 Kelurahan Yosodadi - Iswati Iswati; Heri Cahyono; Sujino Sujino; Prabowo Prabowo; Majmuatur Rosail; Desti Amelia; Nur Azizah; Siwi Asabilul Wahidah; Isa Alawi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This service aims to increase the attractiveness of potential customers for MSME products in RT 03 RW 06 Yosodadi Village through training in copywriting techniques on social media. Effective copywriting is the key to introducing products persuasively and building engagement with consumers. The training participants involved participants from MSME actors in the RT. The training method involves theory and practice sessions, with a focus on copywriting strategies that suit the characteristics of social media. In addition, monitoring and evaluation of training results is carried out to measure increases in product attractiveness and interaction on social media. It is hoped that the results of this research can make a positive contribution in strengthening the branding and marketing of MSME products at the local level, creating sustainable business opportunities, and providing economic benefits for the community in RT 03 RW 06, Yosodadi Village. The training method implemented involves a participatory approach, where training participants are actively involved in the learning process and developing copywriting strategies. In addition, an analysis of local market characteristics and potential customers' preferences is carried out to adapt the copywriting approach to their needs and desires. This training also provides participants with an understanding of the use of social media as an effective platform for building networks and increasing product visibility. The training material includes techniques for writing attractive titles, using relevant images, and applying persuasive language. Evaluation is carried out through monitoring online interactions, the number of content shares, and the increase in the number of followers or likes. It is hoped that the results of this training can make a positive contribution to increasing sales and popularity of MSME products in the RT 03 RW 06 environment. As an effort to empower the local economy, this research is expected to be able to provide insight to MSME players regarding effective marketing strategies in the digital era, as well as encourage collaboration between MSME actors in increasing the competitiveness of local products in the wider market.